SUSTAINABLE AGRICULTURAL SYSTEM FOR FOOD SOVEREIGNTY: EXPERIENCE FROM SMALLHOLDER SYSTEM IN TAIWAN - M Rondhi; Wen Chi Huang (UNEJ e-Proceeding, 2017)
The issues concerning sustainability and viability of the agricultural sector in Taiwan hasbeen a daunting issues ever since the diversion of the national economy into more centeredon manufacturing and services. In the mean time, Taiwan has faced with ever declining foodself-sufficient rate and became one of the lowest in Asia with a mere 31% by calorie in 2015.Explanations have been made such as it is a fact that the vast importation is used for animalfeed or food processing, yet, it also reflected the challenges for the agricultural sector. Themajor challenges included fragmented and declining farmland size, aging faming population,increased set-aside and especially low food self-sufficiency rate. As indicated in the recentlyreleased initial census report for 2015, more than 80% of the faming family were cultivatingon less than 1 ha of farmland and the average age of the farm owner-operator was 63.5 yearsold. As such, agro-food policy is a national security issue: as it closely link to the welfare ofthe stakeholders, farmers, food industry, consumers, future generations. Food sovereigntyperspectives can be an interesting dimension to address the ability of the nation to respondto the multiple stokeholds involved. Food is a culture, yet it is a dynamic process. Therefore, itis important to understand the dynamic of food preference and choice over time as thepopulation structure changes, and how the agricultural sector can respond to it. This reportintended to present recent new initiatives in Taiwan to address these issues.